Pengaruh Variasi Temperatur Tempering Terhadap Struktur Mikro Dan Struktur Kristal Pada Baja Karbon Sebagai Bahan Mandrill - Ikhrar Damai Tullah; Yulius Nanang; Budiarto Budiarto (Politeknik Negeri Padang, 2023)
This writing begins with a mandrill that cannot be modified in a company, so the author wants to know the crystal structure and microstructure of the steel, as well as explain the composition contained in the steel being tested. Tests were carried out by observing the crystal structure using an X-Ray Diffractometer (XRD), observing the microstructure and material composition using Scanning Electron Microscopy – Energy Dispersive X-ray (SEM-EDX). The results show that the crystal structure and microstructure are strongly influenced by the quenching and tempering processes. The increase in crystal size occurred after the tempering process at 425° C from 34.33 nm to 52.31 nm. There was a decrease in dislocation density after tempering at 425° C from 0.00085 lines/mm2 to 0.00085 lines/mm2. Likewise, the micro strain after the tempering process at 425°C decreased from 0.25 (ε) to 0.19 (ε). The test material has several compositions such as iron (Fe), oxygen (O), manganese (Mn), sodium (Na), chromium (Cr), calcium (Ca) and carbon (C). Microstructure testing showed a decrease in iron Fe atoms after the tempering process from 65.79% to 42.96%, a decrease in atoms also occurred in manganese from 0.51% to 0.34% after the tempering process. There was an increase in oxygen atoms after the tempering process from 33.31% to 54.23%, an increase in the atomic presentation also occurred in sodium (Na) from 0.33% to 2.46% after the tempering process